(untitled) (Journal of NELTA, 2013)
This study mainly focused on exploring the efficacy of applying the communicative approach to teaching German at the Goethe Institute in Bangladesh. A qualitative approach was used to collect data by using journal writing by the teacher as well as informal feedback from students. The students comprised 11 schoolteachers from a number of Bangladeshi English-medium schools. Since emphasis was given on testing reading and writing rather than on evaluation of all four skills, applying CLT was tailored to teaching reading and writing rather than speaking and listening with the effect that students at the end of the course had elementary knowledge of reading and writing but poor knowledge of speaking and listening. The question that follows is how communicative is the communicative approach if testing clashes with pedagogy? This article explores the limitations of applying CLT to the German language class and the dilemma that comes with it as to which approach is the best approach to teach a foreign language. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 83-92 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8095